Control biológico del picudo de las bananeras Cosmopolites sordidus Germar con el uso de varias cepas Beauveria bassiana en condiciones de laboratorio - Ronquillo Moran, Andy Ramón (2021)
The study was carried out in the environment of the Entomology Laboratory of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at Km 7.5 of the Babahoyo - Montalvo road. The plane coordinates of a point in the center of the research area are: longitude - 1.797222 m and latitude -79.484171 m of zone 17, according to the UTM projection and the WGS84 reference system. The distance between each Petri dish containing the adult C. sordidus inoculated with B. bassiana is 0.10 m, as described below: C. sordidus insects in larva, pupa and adult stages were collected from the corms of affected banana plants in the field, where a palìn was used to extract the corms with galleries, which were taken to the Entomology Laboratory. Before entering the Entomology Laboratory, all debris or impurities from the corms were cleaned with water and then disinfected with 0.5% sodium hypochlorite to avoid any type of contamination. The inoculation of the fungus in the adult insects of C. sordidus was carried out by microaspersion with micropipettes, dispersing the spores of B. bassiana in the dorsal part of the adult insect with 5 days of emergence. The inoculated adult insects were placed in Petri dishes with 30 g of pseudostem and 30 g of fresh corm, which were previously disinfected in boiling water for a period of 60 seconds. For each treatment, 5 adult insects were placed in three replicates, evaluated every 5, 8 and 10 days after inoculation. Treatment 8 (BbPLUS (B. bassiana) 11.5 ml/L) and treatment 9 (BbPLUS (B. bassiana) 12.5 ml/L), presented the highest number of dead insects, 8 days after inoculation.